2016
DOI: 10.1353/cpr.2016.0052
|View full text |Cite
|
Sign up to set email alerts
|

Partnership Among Peers: Lessons Learned From the Development of a Community Organization–Academic Research Training Program

Abstract: Background Community engagement and rigorous science are necessary to address health issues. Increasingly, community health organizations are asked to partner in research. To strengthen such community organization–academic partnerships, increase research capacity in community organizations, and facilitate equitable partnered research, the Partners in Education Evaluation and Research (PEER) program was developed. The program implements an 18-month structured research curriculum for one mid-level employee of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…High variability was found during critical appraisal of case studies, with scores ranging from 1 to 10 (Akintobi et al., ; Caldwell et al., ; Chaskin, Goerge, Skyles, & Guiltinan, ; Darling et al., ; LoConte, Weeth‐Feinstein, Conlon, & Scott, ; McFarlane, Kahili, & Johnson, ; Napoles et al., ; Panapasa et al., ; Singer et al., ). Five studies met all the criteria (Chaskin et al., ; Darling et al., ; Gainforth, Latimer‐Cheung, Moore, Athanasopoulos, & Martin Ginis, ; Jewett‐Tennant et al., ; Woodruff et al., ). Points were deducted from case studies that did not describe the methods, analysis and results for the project itself (Caldwell et al., ; Panapasa et al., ; Singer et al., ; Tisnado et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…High variability was found during critical appraisal of case studies, with scores ranging from 1 to 10 (Akintobi et al., ; Caldwell et al., ; Chaskin, Goerge, Skyles, & Guiltinan, ; Darling et al., ; LoConte, Weeth‐Feinstein, Conlon, & Scott, ; McFarlane, Kahili, & Johnson, ; Napoles et al., ; Panapasa et al., ; Singer et al., ). Five studies met all the criteria (Chaskin et al., ; Darling et al., ; Gainforth, Latimer‐Cheung, Moore, Athanasopoulos, & Martin Ginis, ; Jewett‐Tennant et al., ; Woodruff et al., ). Points were deducted from case studies that did not describe the methods, analysis and results for the project itself (Caldwell et al., ; Panapasa et al., ; Singer et al., ; Tisnado et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining studies included quantitative design (Bloom et al, 2009;Chandra et al, 2013;Geist, 2010;Glik et al, 2014;Goytia et al, 2013;Patterson et al, 2011); qualitative design (Boutain & McNees, 2013;Burkhalter et al, 2013;Collignon, Men, & Tan, 2001;Honeycutt et al, 2015;Johnson et al, 2006;Radermacher, Karunarathna, Grace, & Feldman, 2011;Taras et al, 2015); systematic review (Frew et al, 2014); and mixed-method design (Houston et al, 2002;Kakietek et al, 2013;Kelaher et al, 2014 High variability was found during critical appraisal of case studies, with scores ranging from 1 to 10 (Akintobi et al, 2012;Caldwell et al, 2015;Chaskin, Goerge, Skyles, & Guiltinan, 2006;Darling et al, 2015;LoConte, Weeth-Feinstein, Conlon, & Scott, 2013;McFarlane, Kahili, & Johnson, 2014;Napoles et al, 2014;Panapasa et al, 2012;Singer et al, 2015). Five studies met all the criteria (Chaskin et al, 2006;Darling et al, 2015;Gainforth, Latimer-Cheung, Moore, Athanasopoulos, & Martin Ginis, 2015;Jewett-Tennant et al, 2016;Woodruff et al, 2016). Points were deducted from case studies that did not describe the methods, analysis and results for the project itself (Caldwell et al, 2015;Panapasa et al, 2012;Singer et al, 2015;Tisnado et al, 2010).…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dr. Toftle must also anticipate that in a single task force, members lower in the medical hierarchy would remain at risk of testimonial injustice. To counter this possible injustice, she might require that all task force members undergo interprofessional or community-based participatory training, such as that offered at the authors' institution [11,12] and has been advocated as a way of enhancing research capacity [11][12][13]. Such training might also reduce biases that lead to unfair exclusion of some voices.…”
Section: Next Steps For Design Decision Makingmentioning
confidence: 99%